Are wind wave heights increasing in south-eastern south American continental shelf between 321S and 401S? - Dragani, Walter Cesar (2010)
In this paper, a possible increase in wind wave heights in the south-eastern south American continental shelf between 32°S and 40°S is investigated. Both time series of in situ (1996–2006) and topex (1993–2001) annual mean significant wave heights gathered at the continental shelf and adjacent ocean present apparent positive trends. Even though these trends are not statistically different from zero, it must be taken into account that the available in situ and satellite data have a short span and, moreover, in situ data present several gaps. Several papers presented evidence about a possible change on the low atmospheric circulation in this region of the southern hemisphere. Consequently, a weak increase in wave height might be occurring, which would be hard to quantify due to the shortness and the insufficiency of the available observations. In order to study a possible trend in mean annual wind wave heights simulating waves nearshore (swan) model forced with ncep/ncar surface wind was implemented in a regional domain for the period 1971–2005. The annual root-mean-square heights of the simulated wave show significant trends at several locations of the inner continental shelf and the adjacent ocean. The most significant increase is observed between 1991–2000 and 1981–1990 decades. The largest difference (0.20 m, 9%) occurs around 34°S–48°W. The wave height increase is somewhat lower, 7%, in the continental shelf and in the río de la plata estuary. The annual mean energy density (spatially averaged) also presents a significant positive trend (0.036 m2/yr) and relatively high inter-annual variability. The possible link between this inter-annual variability and el niño–southern oscillation (enso) was investigated but no apparent relationship was found. A possible increase in the annual mean energy density of waves would be able to produce changes in the littoral processes and, consequently, in the erosion of the coast.